Cognitive Dissonance-Based Smoking Cessation: Comparing Individual Versus Group Interventions Among University Students - M. Nizar Syarif Hamidi; Syukrianti Syahda; Fitri Apriyanti (Postgraduate, University of Mataram, 2025)
College students' smoking habits reveal cognitive dissonance between their understanding of the risks of smoking and their choice to keep on smoking. This research is to assess the efficacy of cognitive dissonance-based therapies and contrast individual with group strategies in lowering smoking habit in college students. Conducted on 150 smoking college students in Bangkinang City, this research used a randomized controlled trial approach with three parallel groups. Participants were randomly allocated to control (n=50), group intervention (n=50), or individual intervention (n=50). Eight weekly sessions meant to tackle cognitive dissonance made up the intervention. At six-month follow-up, the main result was biochemically confirmed 7-day abstinence. Other results included ongoing abstinence, lower cigarette use, shifts in cognitive dissonance, and self-efficacy. Of the individual group, 38.0%, of the group group, 32.0%, and of the control, 12.0% (p<0.05), this research found 7-day abstinence. Compared to the control, both treatments greatly raised the likelihood of abstinence (individual: OR=4.50, 95% CI:1.65-12.27; group: OR=3.45, 95% CI:1.24-9.62). The two intervention strategies showed no notable change (p=0.519). Changes in cognitive dissonance accounted for 42.1% of the effect of the individual intervention and 38.7% of the impact of the group intervention. While its efficacy was similar to the individual approach, the group intervention (IDR1,875,000 per abstinence) was more efficient than the individual intervention (IDR2,150,000) according to cost-effectiveness analysis. Although its efficacy was similar to the individual approach, the group intervention (IDR1,875,000 per abstinence) was more efficient than the individual intervention (IDR2,150,000). Cognitive dissonance-based interventions were successful in raising abstinence in college smokers; the group approach was more cost-effective. These results back up the use of cognitive dissonance-based treatments in campus smoking cessation programs.